Transfer and loss of allergen‐specific responses via stem cell transplantation: A prospective observational study. Issue 9 (23rd June 2020) - Debiasi, Markus; Pichler, Herbert; Klinglmüller, Florian; Boztug, Heidrun; Schmidthaler, Klara; Rech, Jonas; Scherer, David; Lupinek, Christian; Valenta, Rudolf; Kacinska‐Pfaller, Ewa; Geyeregger, Rene; Fritsch, Gerhard; et al.
Abstract: Background: Currently, no estimates can be made on the impact of hematopoietic stem cell transplantation on allergy transfer or cure of the disease. By using component‐resolved diagnosis, we prospectively investigated 50 donor‐recipient pairs undergoing allogeneic stem cell transplantation. This allowed calculating the rate of transfer or maintenance of allergen‐specific responses in the context of stem cell transplantation. Methods: Allergen‐specific IgE and IgG to 156 allergens was measured pretransplantation in 50 donors and recipients and at 6, 12 and 24 months in recipients post‐transplantation by allergen microarray. Based on a mixed effects model, we determined risks of transfer of allergen‐specific IgE or IgG responses 24 months post‐transplantation. Results: After undergoing stem cell transplantation, 94% of allergen‐specific IgE responses were lost. Two years post‐transplantation, recipients' allergen‐specific IgE was significantly linked to the pretransplantation donor or recipient status. The estimated risk to transfer and maintain individual IgE responses to allergens by stem cell transplantation was 1.7% and 2.3%, respectively. Allergen‐specific IgG, which served as a surrogate marker of maintaining protective IgG responses, was highly associated with the donor's (31.6%) or the recipient's (28%) pretransplantation response. Conclusion: Hematopoietic stem cell transplantation profoundly reduces allergen‐specific IgE responses but also comes with a considerable risk to transfer allergen‐specific immune responses. These findings facilitate clinical decision‐making regarding allergic diseases in the context of hematopoietic stem cell transplantation. In addition, it provides prospective data to estimate the risk of transmitting allergen‐specific responses via hematopoietic stem cell transplantation. Abstract : In this prospective study, children and adolescents undergoing HSCT lost 94% of allergen‐specific IgE responses after transplantation. The risk of transferring or maintaining an allergen‐specific IgE response by HSCT was 1, 7% and 2, 3%, respectively. Donors and recipients should be assessed for allergic diseases before HSCT, and recipients should be followed up by allergists in case of relevant IgE sensitizations in donors or recipients. Abbreviation: HSCT, hematopoietic stem cell transplantation